2020
DOI: 10.7765/9781526153845
|View full text |Cite
|
Sign up to set email alerts
|

Early Anglo-Saxon cemeteries

Abstract: List of gures viii List of tables xii Preface xiii Note on terminology xviii Acknowledgements xx Prologue 1 1 Negotiating early Anglo-Saxon cemetery space 3 2 The syntax of cemetery space 37 3 Mortuary metre 87 4 The grammar of graves 5 Intonation on the individual 6 Early Anglo-Saxon community Epilogue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Here graves can be classified into distinct burial configurations according to orientation, location and frequency of artefacts. We found that burials with CNE ancestry are more often buried in configuration A (located towards the middle of the site and with east-west burial orientation) than in configuration B (located more towards the edges and with north-south orientation) 49 (Fisher's exact test P = 0.048). This shows that there is a significant difference within the treatment of individuals according to their ancestry, a finding very similar to those at early medieval cemeteries in Hungary and Italy with respect to northern versus southern European ancestry 51 .…”
Section: Articlementioning
confidence: 82%
“…Here graves can be classified into distinct burial configurations according to orientation, location and frequency of artefacts. We found that burials with CNE ancestry are more often buried in configuration A (located towards the middle of the site and with east-west burial orientation) than in configuration B (located more towards the edges and with north-south orientation) 49 (Fisher's exact test P = 0.048). This shows that there is a significant difference within the treatment of individuals according to their ancestry, a finding very similar to those at early medieval cemeteries in Hungary and Italy with respect to northern versus southern European ancestry 51 .…”
Section: Articlementioning
confidence: 82%
“…Archaeothanatology, which focuses on the decomposition process and the eventual disarticulation of the skeleton, aims to consider both social and environmental variables in the formation of burial contexts. Important factors in such analyses include the position of the body within the grave; 92 the location, position, and distribution of graves and cemetery features; 93 the placement and arrangement of funerary objects; 94 and the post-burial processes which may impact excavation and interpretation. 95 Such analyses have been used to distinguish the results of postdepositional factors from intentional mortuary behavior, and more recently they have been used to examine symbolic elements in burials.…”
Section: Putting Late Antique Plague Burials In Their Socio-cultural ...mentioning
confidence: 99%
“…Isotopic analysis, for example, has been directed towards establishing the origins of individuals and intrusive groups in Ireland, rather than used to illuminate the effect of religious transformations on diet, subsistence or economy. The potential for this analysis is demonstrated elsewhere (Hannah et al 2018), where more engaged analysis of cemeteries and funerary archaeology has also shown the potential for broaching questions regarding religious specialists, gender, status and hierarchy, which require dedicated study (Livarda et al 2018;Wright 2015a;Sayer 2021). Similarly, the ability of geo-chemical and micromorphological analyses to nuance our understanding of the minutiae of burial ritual is established, but unfulfilled (Pickering et al 2018).…”
Section: Religion and Beliefmentioning
confidence: 99%